Nurses' Knowledge and Practice Concerning Pre and Post-Operative Care in Nineveh Governorate - RifaieYaseen Hameed; Shevan Hassan Mohammed (College of Nursing,University of Mosul, 2018)
A descriptive study was conducted throughout the period (1rst of November/2007 - 16th of August/2008 in order to assess nurse's knowledge and practice concerning pre and post operative care in six general teaching hospitals in Nineveh governorate. The sample of study included (350) nurses of the nursing staff working in those hospitals. An anonymous questionnaire was constructed to gather data concerning the subject of the study. The content validity of tool is determined through a panel (14) of experts, while the reliability of it was measured by applying on (10) nurses, it was (0.89). The finding of the study indicated that (88.29%) of the sample were males, and (13.14%) were graduates of NursingCollege, and (50.57%) of them have less than five years as a duration in nursing experience. The analysis of findings shows that there is no significant differences according to the variable under study, except that of pre-operative knowledge in respect to age and educational variables of nurses. It shows that the excellent percentage of overall knowledge items was (43.1%), overall practice steps was (5.8%), while it was for all together (24.5%). The study concluded that masculine feature threats the feminine feature of the nursing profession and there is a high shortage of advanced nursing certificates. It recommended to enhance the feminism of the profession by various social and legislative arrangements, and appointment of the advanced nursing certificates as well as nursing faculties in the clinical nursing field.